Long Chain Polyunsaturated Fatty Acids in Serum Phospholipids at Birth and the Development of Allergies in the Infants - Engerberg, Sandra (My University, 2013)
Summary Long Chain Polyunsaturated Fatty Acids in Serum Phospholipids at Birth and the Development of Allergies in the Infants The main aim of this thesis was to investigate if the composition of the long chain polyunsaturated fatty acids AA and DHA in umbilical cord serum phospholipids or in maternal serum phospholipids could predict development of eczema, food allergy and asthma in the child at one, four and one and/or four years of age. Another aim was to analyze the correlation between fatty acid levels in maternal serum and cord serum in the mother-infant pairs. Phospholipids of the long chain polyunsaturated fatty acids AA and DHA were extracted from stored maternal serum and cord serum respectively. The serum phospholipids were analyzed using GC-MS. Results was calculated using student’s independent t-test. A questionnaire filled out by participating mothers, gave data of their children’s allergies at one and four years. This data was correlated to the levels of the fatty acids AA and DHA in cord serum phospholipids in order to investigate possible connection. Serum was collected in the year of 1996. Maternal serum samples showed a poor resolution probably due to sample degradation caused by the age of the samples. Cord serum samples, however, showed good resolution, indicating possible presence of antioxidants. Results from cord serum samples were therefore the main focus of this thesis. No correlation between fatty acid levels in cord and maternal serum phospholipids was found, possibly due to the poor resolution of the maternal serum samples. Overall there were no consistently differences found in proportion or amount of AA and DHA in cord serum phospholipids between allergic and non-allergic children at one, four or one and/or four years. However, a pattern of lower levels of both amount and proportion of the fatty acids AA and DHA was found in cord serum phospholipids of allergic children at one and four years. This pattern was found for; eczema, food allergy and asthma. This study showed no consistently differences in proportions or amounts of AA or DHA in cord serum phospholipids between allergic and non-allergic children. Also, the non-existing correlation between fatty acid composition in cord and maternal serum phospholipids implies that there is no association between the child’s allergy development and the mother’s fatty acid composition in serum phospholipids at birth and allergy at one or four years . Hence, the conclusion in this study is that allergy in children at 1 and 4 years of age is not dependent on the fatty acid milieu in serum at birth.
Keywords: Livsvetenskaper; Kemi; Livsmedelsvetenskap; Life Science; Chemical Sciences; Food Science